OUMH1103 Learning Skills for ODL : Tutorial 1; Part 5 - Falilnesa, Mohammad Arfan (2010)
Tutorial 1 covers the first 2 topics of the Learning Skills for Open and Distance Learners module. Topic 1 introduces you to OUMs learning environment and how to manage your learning as an ODL learner while Topic 2 describes online learning environment in OUM. This video lecture is accompanied by sign language.